LC–MS/MS-based multiplex antibacterial platform for therapeutic drug monitoring in intensive care unit patients - Liu, Liang; Zhang, Liu; Zheng, Xiangyi; Liu, Xing; Liu, Wei; Wu, Jianhua (Frontiers in Pharmacology, 2023)
Empirically prescribed standard dosing regimens of antibacterial agents may result in insufficient or excess plasma concentrations with persistently poor clinical outcomes, especially for patients in intensive care units (ICUs). Therapeutic drug monitoring (TDM) of antibacterial agents can guide dose adjustments to benefit patients. In this study, we developed a robust, sensitive, and simple liquid chromatography-tandem mass spectrometry (LC–MS/MS) platform for the quantification of 14 antibacterial and antifungal agents (beta-lactams piperacillin, cefoperazone, and meropenem; beta-lactamase inhibitors tazobactam and sulbactam; antifungal agents fluconazole, caspofungin, posaconazole, and voriconazole; and daptomycin, vancomycin, teicoplanin, linezolid, and tigecycline) that can be used for patients with severe infection. This assay requires only 100 µL of serum with rapid protein precipitation. Chromatographic analysis was performed using a Waters Acquity UPLC C8 column. Three stable isotope-labeled antibacterial agents and one analogue were used as internal standards. Calibration curves ranged from 0.1 –100 μg/mL, 0.1–50 μg/mL, and 0.3–100 μg/mL for different drugs, and all correlation coefficients were greater than 0.9085. Intra- and inter-day imprecision and inaccuracy values were below 15%. After validation, this new method was successfully employed for TDM in routine practice.